Studi Kepatuhan Penggunaan Obat Anti Tuberkulosis pada Pasien Tuberkulosis di Puskesmas Kalibalangan Lampung Utara - Sonia Vicka Farlinza; Fetri Lestari; Ratu Choesrnia (Bandung Conference Series: Pharmacy, 2022)
Abstract. Data from the World Health Organization (WHO) 2019 Globally, it is estimated that there were 10.0 million people suffering from Tuberculosis (TB) disease in 2017. It can be seen in Lampung that there was an increase from 2017-2019, which was 25%-54%. The government estimates that the number of TB sufferers will continue to increase. The increasing number of TB sufferers is caused by various factors, namely the lack of patient compliance for treatment and taking medication. The purpose of this study was to determine the level of adherence to the use of anti-tuberculosis drugs in category 1 tuberculosis patients at the Kalibalangan Health Center, North Lampung Regency. The methodology of this research is a descriptive survey with a cross sectional approach. The data on anti-tuberculosis drug adherence was obtained from MMAS-8 questionnaire filled out by TB patients. 36 respondents were included in the inclusion criteria consisting of 1 respondent (3%) in the low category of compliance, 4 respondents (11%) in the medium category and 31 respondents (86%) in the high category of compliance, and 31 respondents (86%) were in the category of high compliance. The results of the intensive phase TB patient adherence to category 1 TB treatment in this study showed that adherence to taking medication was classified as high. Abstrak. Data dari World Health Organization (WHO) 2019 Secara global, diperkirakan terdapat 10,0 juta orang (kisaran 9,0-11,1 juta) menderita penyakit Tuberkulosis (TB) pada 2017. Berdasarkan data angka penemuan kasus TB (CDR) semua kasus TB Di Provinsi Lampung dapat diketahui terjadi kenaikan dari tahun 2017-2019 yaitu sebesar 25%-54%. Pemerintah memperkirakan jumlah penderita TB akan terus meningkat. Jumlah penderita TB yang meningkat disebabkan oleh berbagai faktor, yakni kurangnya tingkat kepatuhan penderita untuk berobat dan meminum obat. Tujuan dari penelitian ini yaitu untuk mengetahui tingkat kepatuhan penggunaan obat anti tuberkulosis pada pasien tuberkulosis kategori 1 di Puskesmas Kalibalangan Kabupaten Lampung Utara. Metodologi penelitian ini ialah survei deskriptif dengan pendekatan cross sectional. Data kepatuhan minum obat anti tuberkulosis didapatkan dari kuesioner Morisky Medication Adherence Scale-8 (MMAS-8) yang diisi oleh responden penderita Tuberkulosis. Dari hasil temuan didapatkan sebanyak 36 responden yang memenuhi kriteria inklusi. Tingkat kepatuhan dari 36 responden sebanyak 1 responden (3%) masuk dalam kategori kepatuhan rendah, sebanyak 4 responden (11%) masuk dalam kategori kepatuhan sedang, dan 31 responden (86%) masuk dalam kategori kepatuhan tinggi. Hasil kepatuhan pasien TB fase intensif terhadap pengobatan TB kategori 1 pada penelitian ini menunjukkan bahwa kepatuhan minum obat yang tergolong tinggi.